Application of Empirical Bathymetry Method on Sentinel 2A for Measuring Water Depth of Maninjau Lake - Wendi Arifin; Febriandi Febriandi; Muhammad Hanif; Triyatno Triyatno; Ernieza Suhana Mokhtar; Eka Mutia (EPI International Journal of Engineering, 2021)
Lake Maninjau is a lake formed by volcanic activity. Many human activities occur on the catchment area, but also in exploited waters. This study aims to mapping the depth of the waters in the Lake Maninjau and assess the effect of field sample distribution on the quality results of the image transformation. The data used are satellite imagery Sentinel 2A, results of point survey. The analysis technique uses the normalized difference water index algorithm, sun glint, empirical bathymetry method and linear regression. The result of the research which is has found that variations of distribution into the dispersion of the recording process of the depth of the object represented by cell. The depth of the water from the results of this transformation refers to the measurement sample in the field survey. The maximum depth of the waters is in the range of 107m. Shallow waters are predominantly distributed in the northern region which is the out late of Lake Maninjau. The southern area forms a deep basin. The distribution of this sample is in the form of an empirical bathymetry map and the relationship between the results of field measurements and the transformation with a regression value of 0.769, this indicates the consideration of total and distribution of survey sample is influence on quality of the results of the transformation.